2018
DOI: 10.1007/s00128-018-2428-z
|View full text |Cite
|
Sign up to set email alerts
|

Arsenic Bioremediation by Indigenous Heavy Metal Resistant Bacteria of Fly Ash Pond

Abstract: Fly ash (FA), the major by-product of coal-fired thermal power plants, causes significant environmental degradation owing to its injurious heavy metal contents. Leaching of arsenic (As) from ash ponds is especially significant as As released from FA can increase As concentration of drinking water above maximum contaminant level of 10 ppb. The aim of this paper was demonstration of As bioremediation potential of indigenous As resistant bacteria present in the weathered pond ash sample. Ten isolates belonging to… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 29 publications
(6 citation statements)
references
References 21 publications
0
5
0
Order By: Relevance
“…AS-1, Delftia spp. BAs29, Ensifer adhaerens , Micrococcus sp., Pseudomonas chengduensis , and T. arsenivorans (Biswas and Sarkar 2019 ; Biswas et al 2019 ; Corsini et al 2014 ; Ito et al 2012 ; Jebelli et al 2018 ; Lu et al 2018 ; Roychowdhury et al 2018 ; Wan et al 2010 ).…”
Section: Arsenic Microbial Metabolisms and Bioremediationmentioning
confidence: 99%
“…AS-1, Delftia spp. BAs29, Ensifer adhaerens , Micrococcus sp., Pseudomonas chengduensis , and T. arsenivorans (Biswas and Sarkar 2019 ; Biswas et al 2019 ; Corsini et al 2014 ; Ito et al 2012 ; Jebelli et al 2018 ; Lu et al 2018 ; Roychowdhury et al 2018 ; Wan et al 2010 ).…”
Section: Arsenic Microbial Metabolisms and Bioremediationmentioning
confidence: 99%
“…along with toxic elements such as selenium (Se), arsenic (As), vanadium (V), boron (B), aluminium (Al), mercury (Hg), chromium (Cr), lead (Pb), cadmium (Cd), and so forth. These can cause metal(loid)s toxicity in plants (Sushil andBatra 2006, Koukouzas et al 2011;Roychowdhury et al 2018;Gaji c et al, 2016;Gaji c, Djurdjevi c, et al, 2020). The presence of essential elements in FA can be utilised for the growth of plants but if these exceed permissible limits, it results in metal(loid) toxicity (Pandey et al, 2009;Singh et al, 2010).…”
Section: Limitations On Plant Growth On Fa Dumpsitesmentioning
confidence: 99%
“…Consequently, two exopolysaccharide-producing strains were revealed to soak up arsenic within their biomass. Arsenic-resistant heterotrophs versus total heterotrophs counting demonstrated that fly ash was augmented with arsenic-resilient heterotrophs . Chromium is considered to be noxious due to its association with additional metals.…”
Section: Bacteria In Heavy Metal Bioremediationmentioning
confidence: 99%
“…Arsenicresistant heterotrophs versus total heterotrophs counting demonstrated that fly ash was augmented with arsenic-resilient heterotrophs. 82 Chromium is considered to be noxious due to its association with additional metals. In one study, among the isolates from 300 bacteria, strains, namely, Pseudomonas f luorescens and Bacillus safensis, were reported to have the capacity to degrade chromium more than 84% and 72%, respectively; phylogenetic association of 16S rRNA was unwavering by applying bioinformatics, and YKS2 and YPS3 bacterial species were detected with 100% resemblance of sequences.…”
Section: ■ Introductionmentioning
confidence: 99%